The rise of women`s football: a case study of Iceland - Halldorsson, V. (Soccer & Society, 2023)
The women`s national football team of Iceland, from a population of 350,000, has written its name in the history books by qualifying for four consecutive European Championship finals (from 2009), reaching the quarter finals in 2013. However, the women`s team has stood in the shadow of the men`s national football team of Iceland, which has attracted international attention. Thus, in the male-dominated world of football, the success of the women`s team has largely gone unnoticed. This paper seeks to analyze a particular case of the rise of women`s football, as it sheds light on the development and success of Icelandic women`s football and frames this development in a socio-cultural context. More precisely, Icelandic women's football is emerging from within: a relatively gender equal Nordic culture; increased sport professionalism; and general strong national sentiments among Icelanders, which, when combined, have made women players the new and emerging stars of Iceland's football.